Enhancing E-commerce purchase intentions through AI-personalized short videos: An SOR and flow theory perspective - Tong, Gia Tuong; Ho, Phuc Vi Uyen; Vuong, Ngoc Lan Huong; Nguyen, Lu Dinh Khoa; To, Tran Nhu Nguyet (Edelweiss Applied Science and Technology, 2025)
This study examines the determinants of e-commerce purchase intentions in the context of AI-personalized short video recommendations, highlighting the mediating role of immersive experience and the moderating effects of privacy concerns and information quality. A quantitative survey was conducted with 317 experienced online shoppers in Ho Chi Minh City, and data were analyzed using SmartPLS 4 and SPSS 22 to test the proposed relationships. Findings indicate that relevant, inspirational, and emotional experiences significantly enhance immersive experience, with emotional experience exerting the strongest effect. Immersion, in turn, positively influences purchase intentions, serving as a crucial link between experiential stimuli and behavioral response. While privacy concerns weaken and information quality strengthens the relationship between immersion and purchase intention, their moderating effects are relatively minor compared to the direct impact of immersion. The study suggests that e-commerce platforms should optimize AI-driven short video content to emphasize relevance and emotional resonance, while providing accurate, transparent, and appealing product information to enhance conversion and sustain consumer trust. By integrating immersive experience as a central mediator and empirically testing the dual moderating roles of privacy concerns and information quality, this research extends the Stimulus–Organism–Response framework and Flow Theory, offering both theoretical advancement and practical insights for improving the effectiveness of AI personalization in digital commerce.